Delineation of selection criterion using pearson correlation and path coefficient analysis in mutant mungbean (Vigna radiata) lines - RAHEVAR, P M; CHAUHAN, R M; PATEL, P T; SOLANKI, S D; GAMI, R A (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at the research farm of Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat to evaluate plant characteristics associated with grain yield and its attributes in mutant mungbean (Vigna radiata L.) lines in north Gujarat condition through correlation and path analyses during 2019. Eight independent and 1 dependent variable were evaluated for the character association analysis of the 1200 mutant mungbean lines. The uniform, healthy and dry seeds of mungbean variety GM 4 were treated with 4 different doses of gamma rays at B. A. R. C, Trombay, Mumbai during summer 2019. Selection and evaluation was performed till the M2 generation and final M3 generation was grown using augmented design in 21 blocks containing 57 selections and 3 checks. Five plants selected randomly from each replicated lines and subjected to data assortment and analysis using OPSTAT. The seed yield was significantly and positively associated with both number of clusters per plant and number of pods per plant. Same traits, as concluded through the path analysis, had a significant positive direct effect on seed yield. Moderate magnitude of indirect positive effect was detected for number of cluster per plant thorough number of pod per plant (0.162). In order to achieve proper array of relation on seed yield, more traits need to be included in the study, clearly evidenced by the high residual effect of path analysis (0.535). Heatmap interpretation reveals colour grading according to the degree of correlation among the traits. Selection method entered on these 2 traits along with others will be productive to increase seed yield in mungbean.